Non-coding RNAs in Mesenchymal Stem Cell-Derived Extracellular Vesicles: Deciphering Regulatory Roles in Stem Cell Potency, Inflammatory Resolve, and Tissue Regeneration - Fatima, Farah; Ekstrom, Karin; Nazarenko, Irina; Maugeri, Marco; Valadi, Hadi; Hill, Andrew F.; Camussi, Giovanni; Nawaz, Muhammad (Frontiers in Genetics, 2017)
Extracellular vesicles (EVs) are heterogeneous populations of nano- and micro-sized vesicles secreted by various cell types. There is mounting evidence that EVs have widespread roles in transporting proteins, lipids and nucleic acids between cells and serve as mediators of intercellular communication. EVs secreted from stem cells could function as paracrine factors, and appear to mimic and recapitulate several features of their secreting cells. EV-mediated transport of regulatory RNAs provides a novel source of trans-regulation between cells. As such, stem cells have evolved unique forms of paracrine mechanisms for recapitulating their potencies with specialized functions by transporting non-coding RNAs (ncRNAs) via EVs. This includes the dissemination of stem cell-derived EV-ncRNAs and their regulatory effects elicited in differentiation, self-renewal, pluripotency and the induction of reparative programs. Here, we summarize and discuss the therapeutic effects of mesenchymal stem cell-derived EV-ncRNAs in the induction of intrinsic regenerative programs elicited through regulating several mechanisms. Among them, most noticeable are the EV-mediated enrichment of ncRNAs at the injury sites contributing the regulation of matrix remodelling, epithelial mesenchymal transitions and attraction of fibroblasts. Additionally, we emphasize EV-mediated transmission of anti-inflammatory RNAs from stem cells to injury site that potentially orchestrate the resolution of the inflammatory responses and immune alleviation to better facilitate healing processes. Collectively, this knowledge indicates a high value and potential of EV-mediated RNA-based therapeutic approaches in regenerative medicine.